Gravitational radiation, luminous black holes, and gamma-ray burst supernovae - Van Putten, Maurice H. P. M. (Cambridge University Press, 2005)
Gravitational Radiation, Luminous Black Holes and Gamma-Ray Burst Supernovae provides a comprehensive overview of the theory of gravitational radiation and rotating black holes, and the phenomenology of GRB-supernovae. It is ideal for graduate students of gravitational-wave astronomy and as an introduction to those interested in this contemporary development in physics.